Unemployment crisis and ways to remedy it from an Islamic perspective - majdoubeh, Samira. A.; El-Burki, Mustafa. F. (Journal of Risk and Crisis Management, 2021)
The study aimed at show the impact of poverty and unemployment in the threat of members of society, by discussing the concept of unemployment, and following the verses of the Qur’an and Sunah in addressing the unemployment crisis as one of the most important threats to society and showing ways to remedy it, and that the problem of unemployment is one of the global economic problems facing societies and has repercussions on life and all its aspects, and based on the spread of the unemployment crisis in our time, the researcher addressed the topic of "unemployment crisis and ways to remedy it from an Islamic perspective" , where the first topic was about" The definition of unemployment in the language and terminology", the second topic: " unemployment causes and types in Islam", the third topic: " Islam’s view of unemployment and the importance of work", and the fourth topic: Islam’s attitude on unemployment and ways to handle it. The last topic, the researcher explained the results and the effects of the unemployment crisis on the individual and society, and she depended on inductive and inferential method in showing and solving this problem through adherence to the divine approach in its treatment, and find ways to reduce its prevalence. The researcher came up with the most important recommendations. The research recommended the need for the state to adopt the idea of small enterprises and handicrafts that contribute solve unemployment and maintain social security among the segments of society, asking sharia to master the work regardless of its nature because of the serious negative effects of unemployment on the Muslim community Some of the most important results of the research are as follows - The spread of unemployment and poverty among segments of society increases crime and delinquency among members of society. - Spreading awareness of the importance of zakat as it is an essential pillar of Islam, and taking care of its performance to fight unemployment. - Spreading awareness of the importance of work regardless of its nature, because unemployment has serious negative effects on the Muslim community.